La doxografía budista indo-tibetana: una aproximación a sus desarrollos y a su influencia en las clasificaciones occidentales del budismo - Bartolomé Herrero, Jorge (Ílu, 2024)
The doxographical genre (Siddhānta) represents one of the most revealing literary expressions of the Indo-Tibetan Buddhist tradition. Yet in many cases Western approaches to its study have been problematic, which has had a detrimental impact on the Western conceptions on the classification of Buddhist schools of thought. So far, the attempts to remedy the distortions have focused on specific aspects such as revisiting the interpretations of the schools or emphasising the non-historical character of Buddhist doxographical schemes. The present paper aims to make a new proposal for a general review focusing on confronting two aspects: 1) how the Western model developed on the basis of a single Indo-Tibetan scheme; and 2) the existence of a great plurality of proposals within the Buddhist sphere. The first part of the exposition will introduce both the characteristics of the Buddhist doxographical genre and the problems inherent in any doxographical approach, ending with a presentation of the Western model and its main distortions. During the second part, a summary overview of the main developments of the doxographical genre in India and Tibet will be given, highlighting the emergence of the classical model whose impact on the first Western approaches to Buddhism constitutes the last section of the paper.